The silent corner [compact disc, unabridged] : a novel of suspense - Koontz, Dean R. (Dean Ray), 1945- (Koontz, Dean R. (Dean Ray), 1945- Jane Hawk, 2017)
"I very much need to be dead." These are the chilling words left behind by a man who had everything to live for--but took his own life. In the void that remains stands his widow, Jane, surrounded by questions destined to go unanswered . . . unless she does what all the grief, fear, confusion, and fury inside of her demand: find the truth, no matter what. There is no one else to speak for Jane's husband--or the others who have followed him into death at their own hands. Although people of talent and accomplishment, people admired and happy and sound of mind, have recently been committing suicide in surprising numbers, no one else is willing to give up everything, just to seek, to find, to know. No one except Jane. But ahead lies only risk. Because those arrayed against her are legion . . . and dangerously devoted to protecting something profoundly important--or terrifying--enough to exterminate any and all in their way. Too many have already died, and those responsible will learn that all their malevolent power may not be enough to stop a woman as clever as they are cold-blooded, as relentless as they are ruthless--and who is driven by a righteous rage they can never comprehend. Because it is born of love." -- from container.